Goethe, Schelling and the Melancholy of Nature - Federico Vercellone (Rivista di Estetica, 2020)
The relationship between nature and its symbolic and artistic expression is at the centre of Goethe’s reflections during and after his travels in Italy and of Schelling’s thoughts until the period of his philosophy of identity. Here, as is known, Schelling tries to accomplish the project of a new Renaissance, where we can witness an infinite system of correspondences between ideal and real. The symbolical continuity and integration between the two levels includes the presupposition that time and eternity are united. With his dialog Clara or, On Nature’s connection to the spirit world the binding alliance between nature and spirit, on which the possibility of the symbol and then of a new modern mythology is grounded, collapses.